(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The objective of this paper was to present the water quality changes of the one of Polish rivers - Słupia River, located in the Pomeranian Region. The Słupia River receives pollutants derived from non-point and point sources of pollution. This is due to the agricultural and forested character of the river’s basin and the location of the towns of Słupsk and Ustka on the river. The elaboration covers the period from 1988 to 2007 and is based on hydrological data, completed as a part of surface water monitoring programme run by the Inspectorate for Environment Protection and the Institute of Meteorology and Water Management. The changes of physicochemical properties of Słupia River i.e. phosphorus and nitrogen concentrations, BOD5, and amounts of heavy metals were studied. Presented data, showed that the Słupia River has responded to a major nutrient loading reduction. The current concentration of nitrogen and phosphorus form in river allows qualifying the water to first quality class.